Analysis of Notarial Responsibility in Guaranteeing Gender Justice in the Division of Community Property after Divorce - Dwi Utami Asriana Taufik; Devianty Fitri (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2026)
This study examines the responsibility of notaries in ensuring gender justice in the distribution of joint property after divorce. The issue arises from the continued occurrence of unequal distribution of marital assets due to imbalances in power relations between husband and wife, despite positive law emphasizing equality within marriage. This study aims to analyze the scope of notarial responsibility in ensuring gender justice and to examine the civil liability of notaries based on Supreme Court jurisprudence. The research employed a normative juridical method using statutory and case approaches. Data were collected through library research on primary and secondary legal materials and analyzed qualitatively. The results indicate that the responsibility of a notary is not limited to fulfilling formal requirements in deed preparation, but also includes substantial verification regarding defects of consent, imbalance of power relations, and potential harm to weaker parties. Supreme Court Decision Number 1964 K/Pdt/2020 emphasizes balanced distribution of joint property as a form of material justice, while Supreme Court Decision Number 12 K/Pdt/2020 demonstrates that deeds neglecting the rights of wives may be annulled and may result in civil liability for notaries. Therefore, notaries are required to uphold the principle of prudence, provide legal counseling, and refuse the preparation of deeds that contradict justice and legal provisions.